2020
DOI: 10.3390/su12208312
|View full text |Cite
|
Sign up to set email alerts
|

A New Solution for City Distribution to Achieve Environmental Benefits within the Trend of Green Logistics: A Case Study in China

Abstract: Green logistics has become a consensus and an important method to achieve sustainable development in industrial activities. However, the traditional direct distribution mode has high carbon emissions, an uncertain delivery time, and a low delivery efficiency. Uncoordinated resource allocations and unreasonable network layouts of terminal distributions have shackled green development within the express delivery industry. Considering the trend of green logistics, this study innovatively proposes a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge there is no literature investigating the influence of strategy on couriers' order-receiving justice demand and delivery-related information demand. Considering the direct demand of orders for couriers, order delivery directly depends on order assignment and information disclosure strategy (Li and Cai, 2020; Bi et al. , 2020), and this paper investigates the influence of order assignment strategy and delivery-related information disclosure strategy on couriers' justice perception and continuous participation intention.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge there is no literature investigating the influence of strategy on couriers' order-receiving justice demand and delivery-related information demand. Considering the direct demand of orders for couriers, order delivery directly depends on order assignment and information disclosure strategy (Li and Cai, 2020; Bi et al. , 2020), and this paper investigates the influence of order assignment strategy and delivery-related information disclosure strategy on couriers' justice perception and continuous participation intention.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…(2018) investigated the improvement of platform resource utilization and customer experience from order matching strategy in taxi-hailing platforms. In on-demand logistics, orders are the most important resource for couriers, and orders being received and completed depends on order assignment and information disclosure strategy (Li and Cai, 2020; Bi et al. , 2020), and relevant studies found the significant influence order assignment and information disclosure strategy had on platform operational efficiency separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the improvement of income level and the enhancement of environmental awareness, technological innovation not only plays a role in economic development, but also takes environmental protection into account [ 11 , 12 ]. Especially, low-carbon technological innovation is of great significance to carbon emission reduction [ 13 ]. (2) The driving factors of carbon emissions was explored by the IPAT equation and STIRPAT model [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One sector that triggers this problem is the logistics sector (Ibrahim et al, 2020;. Recently, researchers proposed green logistics to overcome this problem (Helo & Ala-Harja, 2018;Bi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%